Expectations and Realities of Engaged Scholarship: Evaluating a Social Economy Collaborative Research Partnership - Karen Heisler; Mary Beckie; Sean Markey (The University of Alabama, 2022)
This paper examines and evaluates the dynamics of engaged scholarship within a complex community-university research partnership. The British Columbia-Alberta Social Economy Research Alliance (BALTA) brings together academics and practitioners with the goal of advancing understanding of the social economy and contributing to the development of a social economy research network in western Canada. Engagement in BALTA refers to both internal (academic and practitioner research partnerships) and external (research process) project components. Our findings indicate that the structure of the project, dictated in large part by funder requirements and the professional cultures of research participants, greatly influenced the nature and quality of engagement. This paper examines the BALTA initiative and the reflexive and adaptive process it has undergone as it responds to various challenges and seeks to realize the ideals and potential of engaged scholarship.